Effect of educational intervention based on health belief model on accident prevention behaviours in mothers of children under 5-years - Elnaz Moridi; Zahra Fazelniya; Asiyeh Yari; Tahereh Gholami; Pooyan Afzali Hasirini; Ali Khani Jeihooni (BMC, 2021)
Abstract Background As the public health problems, accidents are the most important causes of child mortality. The present study aimed to determine the effect of educational intervention based on health belief model on accident prevention behaviors in mothers of children under 5-years of age. Methods This quasi-experimental study was conducted on 200 mothers in Fasa city who were purposefully selected and randomly divided into two groups of intervention and control. Data collection tools were demographic characteristics and health belief model questionnaire. Questionnaires were completed twice before and 3 months after the intervention. After the pre-test, the educational intervention was performed through 6 sessions of 30-35 min in a WhatsApp group. Data were analyzed using SPSS 22 through Chi-square test, independent t-test and paired t-test (p = 0.05). Results The mean age of mothers in the experimental and control groups was 30.14 ± 4.35 and 31.08 ± 4.31 years. Mean score of awareness, perceived sensitivity, perceived severity, perceived benefits, perceived self-efficacy, cues to action, and accident prevention behaviors significantly increased 3 months after the intervention. Conclusion This study showed the effectiveness of educational intervention based on health belief model on accident prevention behaviors in mothers of children under 5-years of age.